Central role for B lymphocytes and CD4(+) T cells in immunity to infection by the attaching and effacing pathogen Citrobacter rodentium - Simmons, Cameron (2018)
Citrobacter rodentium, an attaching-effacing bacterial pathogen, establishes an acute infection of the murine colonic epithelium and induces a mild colitis in immunocompetent mice. This study describes the role of T-cell subsets and B lymphocytes in immunity to C. rodentium. C57Bl/6 mice orally infected with C. rodentium resolved infection within 3 to 4 weeks. Conversely, systemic and colonic tissues of RAG1(-/-) mice orally infected with C. rodentium contained high and sustained pathogen loads, and in the colon this resulted in a severe colitis. C57Bl/6 mice depleted of CD4(+) T cells, but not CD8(+) T cells, were highly susceptible to infection and also developed severe colitis. Mice depleted of CD4(+) T cells also had diminished immunoglobulin G (IgG) and IgA antibody responses to two C. rodentium virulence-associated determinants, i.e., EspA and intimin, despite having a massively increased pathogen burden. Mice with an intact T-cell compartment, but lacking B cells ( micro MT mice), were highly susceptible to C. rodentium infection. Systemic immunity, but not mucosal immunity, could be restored by adoptive transfer of convalescent immune sera to infected micro MT mice. Adoptive transfer of immune B cells, but not naïve B cells, provided highly variable immunity to recipient micro MT mice. The results suggest that B-cell-mediated immune responses are central to resolution of a C. rodentium infection but that the mechanism through which this occurs requires further investigation. These data are relevant to understanding immunity to enteric attaching and effacing bacterial pathogens of humans.